Uniform saturation of a strongly coupled spin system by two-frequency irradiation - Lee, Jae-Seung (American Institute of Physics, 2011)
The theoretical basis of two-frequency saturation is given here in the framework of Provotorov theory. The parameters influencing the saturation efficiency are discussed and studied experimentally using a liquid-crystalline test system. It is shown that double-frequency irradiation can be extremely efficient when the irradiation frequencies are placed at opposite sides of the characteristic frequency of the spin system, and that the frequency separation in the double-frequency irradiation can be varied over a large range. Provotorov theory is also shown to provide good insights into the experimental findings, which would otherwise be difficult to obtain from simulations.